An Extensive Volar Forearm Laceration – The Spaghetti Wrist: A Systematic Review - Kiron Koshy; Rohan Prakash; Andrzej Luckiewicz; Reza Alamouti; Dariush Nikkhah (JPRAS Open, 2018)
Purpose: ‘Spaghetti wrist’ is an extensive laceration that involves multiple structures in the volar wrist, including tendons, nerves and arteries. This injury is frequently encountered in trauma units, but despite its complex nature, management is often handled by junior surgeons.Furthermore, the guidance on how to approach these injuries is limited, with a relatively poor evidence base on management and outcomes. Methods: In this article, we perform a systematic review of the literature on the management and outcomes of the spaghetti wrist injury. Patient demographics, definitions of spaghetti wrist, mechanism of injury, operative and rehabilitative techniques and surgical outcomes are discussed. Results: Results from this study show significant physical, functional, psychological and financial impacts of spaghetti wrist injuries. Operative technique appears relatively consistent; even though reporting of injuries and outcomes was heterogeneous, no current classification system is in common usage. Conclusions: An increased focus on the standardisation of assessment, management and rehabilitation and on overcoming the obstacles to care will serve as a guidance to the operative and post-operative management of the spaghetti wrist injury. The use of a single definition and classification system has been proposed to standardise outcome measures and improve inter-observer reliability. Type of study/level of evidence: Systematic Review: Level IIa evidence Keywords: Injury, Spaghetti, Systematic, Tendon, Trauma